ABPBI-based hollow fiber membranes for forward osmosis (FO) possessing low reverse salt flux - Thorat, Nitin M.; Lele, Ashish K.; Kharul, Ulhas K. (Desalination and Water Treatment, 2024)
The poly(2,5-Benzimidazole), known for its excellent thermochemical stability, was evaluated as a membrane material for forward osmosis. The dope in methane sulfonic acid was used to make hollow fiber membranes. The availability of bound MSA in HFMs was compared with its neutral form. Aqueous solutions of two common salts reported for FO (NaCl and MgCl2) were used as a draw solution at varying concentrations. The performance was determined in terms of water flux and reverse salt flux. The long-term performance of the membrane was assessed. The heat pretreatment of membranes was beneficial in offering low reverse salt flux, a crucial parameter in FO. The heat treatment at 350 degrees C exhibited excellent performance of low-RSF, irrespective of the draw solute used. The presence of MSA in the membrane matrix was found to be beneficial. Present HFMs exhibited reverse salt flux as low as 0.003 mol m-2 h-1 using 2 mol L-1 MgCl2 as a draw solution. The water flux of present membranes was lower than that of reported FO-membranes, which is attributable to the larger thickness of the present membranes. The findings will be used to make ABPBI-based membranes in thin form to elevate the fluxes and their practical applicability.
Keywords: ABPBI; Forward osmosis; Hollow fiber membrane; Low reverse salt flux